Assessment Report on the Ngolo-Batanga Tribal Areas, Kumba Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1922)
This file contains colonial assessment report on Ngolo-Batanga, Kumba Division, Cameroons Province
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies